Analisis Filsafat Pendidikan Ki Hajar Dewantara dalam Perspektif Ontologi, Epistemologi, dan Aksiologi (Indo-MathEdu Intellectuals Journal, 2026)
This research aims to analyze Ki Hajar Dewantara's educational philosophy from the perspectives of ontology, epistemology and axiology and examine its relevance for the development of Indonesian education in the digital era. The research uses a qualitative approach based on library research on the works of Ki Hajar Dewantara and relevant scientific literature. The data collection technique is a documentation method using written sources, both primary and secondary. There are several stages including data tracking, reading, recording and grouping data to facilitate the analysis process. Data analysis uses content analysis techniques to examine Ki Hajar Dewantara's educational paradigm and its implications in contemporary education. The results of the research show that ontologically Ki Hajar Dewantara views humans as virtuous creatures with the potential for creativity, taste and initiative which must be developed in a balanced way through education that guides the nature of nature and the nature of the times. Epistemologically, knowledge is understood as the result of students' experiences, interactions and reflections so that learning places students as active subjects and teachers as guides. Axiologically, education is directed at the formation of humans who are independent, characterized and cultured by emphasizing human values, freedom, example and social responsibility.